A method for designing the logical structure of a distributed telecommunication environment - Vasilyev, G. S.; Eremenko, V. T.; Kuzichkin, O. R.; Eremenko, A. V.; Surzhik, D. I.; Eremenko, S. V. (Revista de la Universidad del Zulia, 2020)
The article presents a methodology for the development of information exchange tools based on the apparatus of hierarchical Petri nets, characterized by the possibility of simultaneous events and allows solving the problem of correctness analysis and verification of protocols. Protocol objects and access points are represented on the basis of the Petri nets apparatus: the simplest object of the reception/transmission protocol, the queue object, a single object and a trivial object. It describes the construction of complex structures of objects and operations on them, the management of timeouts based on the timer object, the specification of protocol objects, the specification of protocols and levels of logical structure. The proposed method is relevant for the analysis of complex communication systems of large size, which are mobile ad-hoc networks with a large number of nodes, characterized by topology instability due to unstable communication channel characteristics and high nodes mobility, and especially flying ad-hoc networks of aircraft (FANET) and flying sensor networks (FSN).